2004
DOI: 10.1182/blood-2004-01-0349
|View full text |Cite
|
Sign up to set email alerts
|

An association of candidate gene haplotypes and bleeding severity in von Willebrand disease (VWD) type 1 pedigrees

Abstract: von Willebrand disease (VWD) type 1 is difficult to diagnose because of bleeding variability and low heritability of von Willebrand factor (VWF) levels. We compared a bleeding severity score and bleeding times to candidate gene haplotypes within pedigrees of 14 index cases, using a covariance components model for multivariate traits (Mendel: QTL Association). These pedigrees included 13 affected and 40 unaffected relatives, as defined by plasma ristocetin cofactor (VWF:RCo) levels. The bleeding severity score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 45 publications
3
46
0
1
Order By: Relevance
“…Even though no additional hemostatic defects were evident, nevertheless we can not exclude that cosegregation with prohemorrhagic polymorphisms in other hemostatic gene(s) might be responsible for this pattern, as recently observed in Type 1 von Willebrand disease [19]. Whatever the explanation is, these results again emphasize the lack of a strict correlation between FXI plasma level and bleeding tendency.…”
Section: Discussionmentioning
confidence: 36%
“…Even though no additional hemostatic defects were evident, nevertheless we can not exclude that cosegregation with prohemorrhagic polymorphisms in other hemostatic gene(s) might be responsible for this pattern, as recently observed in Type 1 von Willebrand disease [19]. Whatever the explanation is, these results again emphasize the lack of a strict correlation between FXI plasma level and bleeding tendency.…”
Section: Discussionmentioning
confidence: 36%
“…In a previous study of VWD type 1 pedigrees [12], we found a significant association between haplotype 2 (807C) and severity of bleeding (high score), while a modest and not statistically insignificant association was seen with -52T. In the case of the type 2 pedigrees in this study, the influence of -52T and its association with increased bleeding score was greater than had been found in the previous type 1 study, while statistical significance was not observed with haplotype 2.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of bleeding episodes was ranked from 0 to 5, as shown in Table 2, in each of 11 bleeding manifestation categories: epistaxis; cutaneous symptomatic bleeding; bleeding from minor wounds; oral cavity bleeding; gastrointestinal bleeding; bleeding associated with tooth extraction; surgery; muscle hematoma; hemarthrosis; postpartum hematoma; and menorrhagia. The bleeding score used in this study, in which a ranking from 0 to 5 is employed, is a modification of the previous scoring method used in our study of VWD type 1 patients [12] in order to more fully describe the severity of bleeding in all 11 categories. The numerical sum of the scores for each category was then divided by the age of the individual and multiplied by 100 to arrive at the bleeding severity score adjusted for age.…”
Section: Standardized Criteria To Evaluate Bleeding Historymentioning
confidence: 99%
“…14 Genotypes were determined using primer sequences in a primer extension based assay 15 or a customized Nanogen-based single nucleotide polymorphism (SNP) analysis (Nanogen Inc., San Diego, CA, USA). 16 SNPs were confirmed by direct Sanger sequencing.…”
Section: Design and Methodsmentioning
confidence: 99%